(untitled) (Research, Society and Development, 2020)
Objective: To analyze, in the ecosystem context, the professional visibility of the members of the Bone Marrow Transplantation team, in the user’s view. Methods: Quali-quantitative approach, using Bardin Content Analysis and descriptive statistical analysis of results, employing the Statistical Package for the Social Sciences. Frequency analysis, percentage of observed variables and statistical analysis of interval estimation were performed. In data collection, an instrument with 35 questions was used. The sample consists of 40 interviewees in two transplant services in two countries. Results: The data show that users viewed more than one professional to offer guidance for care at home. 90% (n=36) answered that it was the doctor who guided the most to discharge; 72.5% (n=29) reported the nurse, 42.5% (n=17) the nutritionist and 27.5% (n=11) cited the care of other professionals. Conclusion: The professional visibility of transplant team members, in the user’s view, also proved to be influenced by the biomedical health model, gradually evolving to identify professional representative activities, through the conquest of the spaces destined for each member in the transplant health team in relation to guidelines for hospital discharge after transplantation.